Coronary Angiographic Characteristics of Patients with First Myocardial Infarction Admitted in a Tertiary Care Cardiac Hospital in Bangladesh - Kabiruzzaman, M; Ali, MA; Islam, MN (Cardiovascular Journal, 2010)
Background: Coronary artery lesion characteristics of patients with First myocardial infarction (First MI) of Indian subcontinent origin in UK, is different from indigenous white population. The present study was aimed to observe coronary angiographic profile of first MI patients, hospitalized in a tertiary care hospital, in Bangladesh and to compare the results with published data of study done home and abroad. Methods: This is a prospective observational study. A total of 100 cases of First MI patients were included in this study. Clinical history, physical examination, major risk factors, relevant investigations including ECG & Echocardiogram and coronary angiogram of all patients were recorded. Results: The coronary angiographic features of 100 patients revealed that 88% of the study population had significant coronary artery lesion (stenosis e”70%). Normal coronary arteriogram was found in 5 patients (5%); although they had myocardial infarction previously. Insignificant lesion (stenosis < 70%) was detected in 7 patients (7%). Left anterior descending (LAD) arteries were affected in most of the patients (78%), followed by right coronary artery (62%) and left circumflex artery (55%). Single vessel disease (33%) and triple vessel diseases were equally prevalent among the study population. Conclusion: Present study observed that triple vessel disease, diffuse pattern of lesions and combined type of lesions were more prevalent among the first MI patients. Increase in the number of risk factors was associated with progressive increase in severity of disease as defined by number of significant stenosis. Comparison of results of present study population with that of study done abroad shows that single vessel disease was more prevalent among European white patients who had first MI but triple vessel disease was more prevalent among our patients. Keywords: First MI; Coronary angiogram. DOI: 10.3329/cardio.v2i2.6640 Cardiovasc. j. 2010; 2(2) : 204-211